PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI MADRASAH IBTIDAIYAH MI’RAJUL ULUM TELUK BERINGIN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Lestari Rahayu; Bustanur Bustanur; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This study aims to determine the influence of the principal's leadership on teacher performance at MI Mi'rajulUlum TelukBeringin, Gunung Toar District, Kuantan Singingi Regency, and to determine the factors that influence the principal's leadership on teacher performance at MI Mi'rajul Ulum Teluk Beringin Subdistrict. Mount Toar, Kuantan Singingi Regency.The results of observations made at MIMi'rajulUlumTelukBeringin, GunungToar District, Kuantan Singingi Regency showed the following symptoms: 1) There are still teachers who are not professional in carrying out their duties. 2) There are still teachers who teach not according to their field. 3) Lack of teacher motivation in carrying out their duties. 4) There are still teachers who come late to class and do not complete their assignments on time. The data collection technique uses a simple linear regression analysis technique with the help of SPSS Based on the percentage achieved in this study, it can be seen that the principal at MI Mi'rajul Ulum Teluk Beringin, Gunung Toar District, Kuantan Singingi Regency made a significant contribution. The regression equation is Y-13.43+1.079X. From this equation the value of the principal's leadership coefficient is 1.079 which means, if the principal's leadership increases by one unit, the teacher's performance will increase by 1.079 units. After knowing the influence between the two variables, then proceed with finding the value of the coefficient of determination on teacher performance. Thus, the magnitude of the influence of the principal's leadership on the performance of teachers at MI Mi'rajul Ulum Teluk Beringin, GunungToar District, KuantanSingingi Regency is 77.4% which means it has an influence while 22.6% is influenced by other factors.